The Hyperdense Internal Carotid Artery Sign: Prevalence and Prognostic Relevance in Stroke Thrombolysis - P. R. Fitzsimmons; S. Biswas; A. M. Hill; R. Kumar; C. Cullen; R. P. White; A. K. Sharma; R. Durairaj (Stroke Research and Treatment)
Introduction. The hyperdense internal carotid artery sign (HICAS) has been suggested as a common marker of terminal internal carotid artery (ICA) thrombus associated with poor outcomes following thrombolysis. We aimed to investigate the prevalence and prognostic significance of the HICAS in an unselected cohort of patients receiving intravenous thrombolysis. Methods. Prethrombolysis NCCTs of 120 patients were examined for the presence of the HICAS and hyperdense middle cerebral artery sign (HMCAS). A poor outcome was defined as a discharge Barthel score <15 or inpatient death. Results. A HICAS was present in 3 patients (2.5%). Prethrombolysis neurological deficits were significantly more severe in patients with a HICAS (𝑃=0.019). HICAS was not significantly associated with a poor outcome (𝑃=0.323). HMCAS was significantly associated with severe prethrombolysis neurological deficits (𝑃=0.0025) and a poor outcome (𝑃=0.015). Conclusions. This study suggests that the prevalence of the HICAS may be lower than previously reported. The presence of a HICAS was associated with severe prethrombolysis neurological deficits in keeping with terminal ICA occlusion. The role of the HICAS as a prognostic marker in stroke thrombolysis remains unclear.